CO Multi-line Imaging of Nearby Galaxies (COMING). II. Transitions between atomic and molecular gas, diffuse and dense gas, gas and stars in the dwarf galaxy NGC 2976. (1st July 2017) - Hatakeyama, Takuya; Kuno, Nario; Sorai, Kazuo; Kaneko, Hiroyuki; Miyamoto, Yusuke; Muraoka, Kazuyuki; Takeda, Miho; Yanagitani, Kazuki; Kishida, Nozomi; Umei, Michiko; Tanaka, Takahiro; Tomiyasu, Yuto; et al.
Abstract: In this study, we present the results of 12 CO( J = 1–0), 13 CO( J = 1–0), and C 18 O( J = 1–0) simultaneous observations of the dwarf galaxy NGC 2976 conducted as a part of the CO Multi-line Imaging of Nearby Galaxies (COMING) project using the Nobeyama 45 m telescope. We investigated the properties of the molecular gas and star formation in NGC 2976. We found that the molecular gas fraction depends on the surface densities of the total gas and the star formation rate, according to the main stellar disks of spiral galaxies. The ratio of 12 CO( J = 3–2) to 12 CO( J = 1–0) implies that the temperature of the molecular gas increases with decreases in the surface density of molecular gas. We detected 13 CO( J = 1–0) by using the stacking method. The ratio between the integrated intensities of 12 CO( J = 1–0) and 13 CO( J = 1–0) was 27 ± 11. These ratios imply that the diffuse gas phase is dominant in low surface density regimes. We obtained a lower limit of the ratio between the integrated intensities of 12 CO( J = 1–0) and C 18 O( J = 1–0) of 21. The relation between the surface densities of the total gas and the star formation rate followed a power-law index of 2.08 ± 0.11, which was larger than that between the surface densities of the molecular gas and the star formation rate (1.62 ± 0.17). The steep slope in the relation between the surface densities of the total gas and the star formation rate can be attributed to the rapid increase in the fraction of molecular gas at the surface density of ∼ 10 M ⊙ . The kinematics of the molecular gas suggest that the bar-like feature rotates with a rigid-body rotation curve rather than a certain pattern speed.